PENGARUH STRUKTUR MODAL TERHADAP KINERJA PERUSAHAAN BERDASARKAN SIKLUS HIDUP PERUSAHAAN PADA MASA COVID-19 - Mantini Kriswanti; Lina Nabilah Daulay; Alis Akbar; Eddy Suranta (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to examine the effect of capital structure on company performance based on the company's life cycle during the COVID-19 period. The population used in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX), but in this study only 76 companies were sampled. The capital structure in this study uses the ratio of total debt to total equity, and the company's performance uses the ratio of net income to total assets. The company life cycle in this study uses cash flow patterns from operating, investing, and financing activities. In this study, capital structure has a negative effect on company performance at the introduction, growth, and decline stages. However, the capital structure does not affect the company's performance at the mature and shakeout stages.